Exploring changes in the lives of the ultra poor: an exploratory study on CFPR/TUP members - Malin, lmran; Walker, Sarah (BRAC, 2019)
Since January 2002, BRAC has started a new experimental programme for the ultra poor called, 'Challenging the Frontiers of Poverty Reduction/Targeting the Ultra Poor' (CFPRffUP). This programme targets the ultra poor who are either bypassed or fail to benefit and subsequently drop out from existing development programme. The programme uses an asset-based approach where physical assets are provided to the selected ultra poor women as grants. The intervention strategy also includes health and social development components. The overall idea of the programme is to strengthen the physical, social and human asset base of the ultra poor so that once the grant phase is over, they can attain the foundation for sustainable livelihoods, and participate and benefit from mainstream development programmes. This paper is based on an exploratory study that wanted to better understand the perceptions of change as defined by the programme members and the underlying factors that explain the changes perceived. The main finding is that initial conditions matter - households that owned homestead land, had other sources of income, had adult male labour power and did not suffer from recurrent health costs did better. The programme encouraged the members to save out of the income accrued from running the TUP enterprise, but the product was focussed on supporting the promotional needs rather than protectional needs. The circumstances of the ultra poor households differ and a sole focus on the .savings for meeting the promotional needs may thus need reconsideration .